Umur Ibu Waktu Melahirkan Dan berat lahir bayi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
ABSTRACT Maternal age and birth weight data of 2,784 mothers who had their ANC and delivery of live singletons in 27 Private Maternity Clinics in the Wonogiri District, Central Java, from January until December 1989, were cross-tabulated. Controlling for parity, the Relative Risk (PR) and Attributable Risk (AR) values were calculated for tables with increasing maternal age cut-off points (from 20 to 35) and 2 different LBW upper limits (5 2,500 gr and < 2,500 gr). Two hundred-eighty-six (10.3%) mothers delivered 5 2,500 gr babies or 162 (5.8%) mothers delivered < 2,500 grbabies. One hundred-sixty-five (5.9%) of the mothers were less than 20 years of age and 156 (5.6%) were 35 or more. The highest RR and AR values were attained when mothers delivered their second child below the age of 20 (respectively, 5.80 and 17.5% for S 2,500 gr LBW upper limit and 9.82 and 29.9% for < 2,500 gr LBW upper limit) and their first child at the age of 29 or over (respectively, 3.19 and 19.6% for 5 2,500 gr LBW upper limit and 6.61 and 24.3% for < 2,500 gr LBW upper limit).